Solar Reforming of Biomass with Homogeneous Carbon Dots. Issue 41 (1st September 2020) - Achilleos, Demetra S.; Yang, Wenxing; Kasap, Hatice; Savateev, Aleksandr; Markushyna, Yevheniia; Durrant, James R.; Reisner, Erwin
Abstract: A sunlight‐powered process is reported that employs carbon dots (CDs) as light absorbers for the conversion of lignocellulose into sustainable H2 fuel and organics. This photocatalytic system operates in pure and untreated sea water at benign pH (2–8) and ambient temperature and pressure. The CDs can be produced in a scalable synthesis directly from biomass itself and their solubility allows for good interactions with the insoluble biomass substrates. They also display excellent photophysical properties with a high fraction of long‐lived charge carriers and the availability of a reductive and an oxidative quenching pathway. The presented CD‐based biomass photoconversion system opens new avenues for sustainable, practical, and renewable fuel production through biomass valorization. Abstract : Biomass‐derived materials photoconvert biomass: A triple natural resource system is reported that uses solar energy to convert biomass from untreated water into sustainable H2 and organics. The process is photocatalyzed by scalable carbon dots produced from α‐cellulose that act as water‐soluble light absorbers to photoconvert lignocellulose with a Ni cocatalyst. The carbon dots function under ambient conditions and benign aqueous solution.